The Role of Satisfaction Customer Mediate Influence Perception Quality To Loyalty Customer - Putu Pujashanti Wilothama; Ni Made Purnami (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
iPhone is one of the premium smartphones that Apple relies on to compete with various premium smartphone products from other brands. The iPhone has a competitive advantage in the form of a unique and exclusive physical design and an operating system that is different from other brands in order to maintain its existence in the market. This study aims to explain the role of customer satisfaction in mediating the influence of quality perception on customer loyalty in iPhone smartphone users in Denpasar City. This study used a sample of 100 respondents taken using the non-probability sampling method with purposive sampling techniques. The data in this study was collected using a questionnaire method which was distributed in the form of a google form link to respondents. The data that has been collected is then analyzed and tested using classical assumption tests, path analysis tests, and testing the role of mediating variables. The results of this study show that quality perception has a positive and significant effect on customer loyalty, quality perception has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, and customer satisfaction is able to partially mediate the influence of quality perception on customer loyalty. The results of this study can provide suggestions for Apple companies to improve the perception of quality and customer satisfaction in iPhone users to increase customer loyalty.